2019
DOI: 10.4274/tjh.galenos.2019.2019.0166
|View full text |Cite
|
Sign up to set email alerts
|

First-Time Blood Donors are Double Edged Swords for Blood Transfusion Centers: a Retrospective Study in Southwest Iran

Abstract: Objective: First-time blood donors are the most common group of blood donors. They usually have different motivations for blood donation, some of which provoke the donors to hide risk factors of transfusion-transmissible infections (TTIs). Therefore, detection of TTIs among first-time donors is crucial and can decrease the rate of TTIs among blood recipients. This study aimed to evaluate the prevalence of TTIs among first-time donors in the transfusion center of Kohgiluyeh and Boyer-Ahmad Province (KBTC), Iran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 23 publications
0
9
1
Order By: Relevance
“…33 This finding may indicate the likelihood that the prevalence of HBV in the general healthy population is relatively high. Our findings were on the lower side when compared with studies from Sudan (11.7%), 25 and Tanzania (8.8%), 39 and slightly higher from Iran (0.13%), 37 Brazil (1.63%), 40 and Bangladesh (1.4%). 41 The overall prevalence of HIV in the present study was 0.23%.…”
Section: Discussioncontrasting
confidence: 79%
See 3 more Smart Citations
“…33 This finding may indicate the likelihood that the prevalence of HBV in the general healthy population is relatively high. Our findings were on the lower side when compared with studies from Sudan (11.7%), 25 and Tanzania (8.8%), 39 and slightly higher from Iran (0.13%), 37 Brazil (1.63%), 40 and Bangladesh (1.4%). 41 The overall prevalence of HIV in the present study was 0.23%.…”
Section: Discussioncontrasting
confidence: 79%
“…33 The possible reason could be the high percentage of voluntary blood donors in our study. When compared with global studies, the prevalence was lower when compared with those reported from Egypt (4.3%), 34 Kenya (3.21%), 35 and Sudan (3.4%) 36 while it was higher when compared with studies from Iran (0.07%), 37 Ethiopia (0.6%), 15 Saudi Arabia (0.40%), 38 and India (0.06%). 27 The overall prevalence of hepatitis B in our study was 1.95%.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Blood safety is the most concern of blood transfusion worldwide (12). Therefore to ensure blood safety, the history of previous transfusions and hematological disorders must be taken into account before performing any blood transfusion.…”
Section: Discussionmentioning
confidence: 99%